Science and technology as transforming elements of nature in the Golfito division, Costa Rica. (1938-1962) - Conejo Barboza, Luis (2019)
One of the main justifications used by the United Fruit Company to legitimize its entry and stay in the Central American region was the arrival of the science and technology brought by it. In that sense, it is important to study the way in which the transnational managed to consolidate that representation in both the American and Central American publics. Likewise, the history of the company and its representation of science and technology are also the continuity of a construction that developed the confrontation between nature and science in American history. It is based on the case study of the Golfito division, to explain the means used by the transnational to legitimize and build that representation.